Retort-resistant, highly transparent, and highly barrier cyclic olefin copolymer film and its preparation process

By adopting three-layer coextruded film structure and modified polypropylene, layered double hydroxide and other materials, the problem of insufficient light transmittance after high temperature sterilization of cycloolefin copolymer film is solved, and the effects of high transparency and high barrier are achieved.

CN119348264BActive Publication Date: 2025-03-14SHANDONG YONGJU MEDICAL TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411886638.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-14
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

The cycloolefin copolymer film has a light transmittance of less than 85% after sterilization at high temperature of 121°C, which limits the intuitive observation of food or drugs and increases safety hazards.

Method used

The three-layer coextruded film structure is adopted, and the multi-layer film structure design of the inner layer, the middle layer and the outer layer is designed, and modified polypropylene and layered double hydroxide are used to improve the light transmittance and barrier properties of the film material.

Benefits of technology

The cycloolefin copolymer film has achieved a light transmittance of more than 92% after sterilization at high temperature of 121°C, which significantly improves the barrier properties and light transmittance of the film material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119348264B_ABST
    Figure CN119348264B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of food packaging or pharmaceutical packaging materials, and specifically relates to a boiling-resistant, highly transparent, high-barrier cyclic olefin copolymer film and its preparation process. The boiling-resistant, highly transparent, high-barrier cyclic olefin copolymer film is a three-layer co-extruded film, and the layer structure is shown in FIG1 , which consists of an inner layer, an intermediate layer, and an outer layer, and is made of the following raw materials: inner layer: COC, toughening agent, modified ternary random copolymer polypropylene; intermediate layer: COC, toughening agent, modified binary random copolymer polypropylene, layered double hydroxide; outer layer: COP, toughening agent, modified binary random copolymer polypropylene, layered double hydroxide; the present invention utilizes the characteristics of the multilayer film structure, with a high-performance modified COP layer as the outer layer, to solve the problem of reduced transmittance caused by high-temperature ring opening of the copolymerized ethylene monomer and norbornene in COC and the formation of hydroxyl groups with water molecules, and the transmittance of the cyclic olefin copolymer film reaches more than 95% after high-temperature sterilization at 121°C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of food packaging or medicine packaging materials, and in particular relates to a boiling-resistant high-transparency high-barrier cyclic olefin copolymer film and a preparation process thereof. Background Art

[0002] Cyclic olefin copolymer (COC) is an amorphous polyolefin with a macrocyclic structure in the main chain, which is copolymerized by ethylene and norbornene. Compared with traditional packaging materials, COC plastic has good biocompatibility, excellent barrier properties and high mechanical strength, making it an ideal candidate for food packaging and pharmaceutical packaging.

[0003] Patent CN114211840A discloses a high barrier infusion film and its preparation method. The prepared high barrier infusion film includes a moisture barrier layer, a gas barrier layer, a reinforcement layer and an outer layer, and there is an adhesive layer between two adjacent layers. This patent makes the infusion film have excellent gas and water vapor barrier properties through a multi-layer composite method. Different from the above patents, patent CN115384149A discloses a modified COC barrier film material and its preparation method. This invention uses a small amount of organic nano-silicate and polyethylene and COC to prepare a barrier film. By introducing organic nano-silicate into the film material, the film material not only has excellent mechanical properties but also has excellent oxygen and water vapor barrier properties. Therefore, it can be widely used in food contact materials and pharmaceutical packaging materials. In addition, patent CN116200008A provides a method for preparing a modified cycloolefin polymer barrier material, which introduces modified organic silicate nanomaterials and polyethylene into modified cycloolefin polymer (COP). Through the combined effect of the two, the oxygen barrier performance of the COP film is significantly improved without reducing the comprehensive performance of the cycloolefin polymer material. Finally, Chinese patent CN115384149A discloses a method for preparing a high-barrier single-material polymer film. Using COC as the base film layer, a dense coating is formed on the surface of the COC vapor-deposited substrate layer by evaporation, which solves the problem of poor barrier performance of the single-material packaging film.

[0004] Although the above methods achieve high barrier properties of COC films through compounding, modification or evaporation, further expanding the application of COC packaging materials. However, the light transmittance of COC film products after high-temperature (121°C) sterilization is generally less than 85%, which seriously limits the intuitive observation of food or medicine, and increases safety risks sharply. Therefore, without reducing the comprehensive performance of cycloolefin polymer materials, improving the light transmittance of cycloolefin copolymer film products after high-temperature sterilization has become a key issue that needs to be solved for COC packaging materials. Summary of the invention

[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a highly transparent and high-barrier cyclic olefin copolymer film that is resistant to boiling. After being sterilized at a high temperature of 121°C, the light transmittance of the product reaches more than 92%.

[0006] The present invention also provides a preparation process thereof, which solves the problem that cycloolefin polymer (COP) is too rigid to be used for blow molding preparation, and the light transmittance of cycloolefin copolymer (COC) is less than 85% after being sterilized at a high temperature of 121°C.

[0007] The boiling-resistant, highly transparent, and highly barrier cyclic olefin copolymer film of the present invention is a three-layer co-extruded film, and the layer structure is as follows: Figure 1 As shown, it consists of an inner layer, a middle layer and an outer layer, and is made of the following raw materials in parts by weight:

[0008] Inner Layer:

[0009] Cyclic olefin copolymer: 70.0-80.0 parts;

[0010] Toughening agent: 10.0~20.0 parts;

[0011] Modified ternary random copolymer polypropylene: 10 parts;

[0012] Middle layer:

[0013] Cyclic olefin copolymer: 60.0-70.0 parts;

[0014] Toughening agent: 20.0~30.0 parts;

[0015] Modified binary random copolymer polypropylene: 10 parts;

[0016] Layered double hydroxide: 1.0-3.0 parts;

[0017] Outer Layer:

[0018] Cycloolefin polymer: 60.0-70.0 parts;

[0019] Toughening agent: 20.0~30.0 parts;

[0020] Modified binary random copolymer polypropylene: 10 parts;

[0021] Layered double hydroxide: 1.0-3.0 parts;

[0022] The total thickness of the cycloolefin copolymer film is 175-225 μm, wherein the inner layer accounts for 15.0-25.0% of the total thickness, the middle layer accounts for 50.0-70.0% of the total thickness, and the outer layer accounts for 15.0-30.0% of the total thickness.

[0023] The toughening agent is one or more of styrene-ethylene-butylene-styrene block copolymer (SEBS), thermoplastic polyurethane elastomer (TPU), and polyolefin elastomer (POE).

[0024] The layered double hydroxide is one of magnesium aluminum layered double hydroxide, zinc aluminum layered double hydroxide, zinc nickel aluminum layered double hydroxide, and aluminum calcium layered double hydroxide, and has a size of 100 nm, among which magnesium aluminum layered double hydroxide is preferred.

[0025] The modified binary random copolymer polypropylene and modified ternary random copolymer polypropylene are modified by introducing nano silicon dioxide.

[0026] The size of the nano silicon dioxide is 25-35nm.

[0027] The preparation process of the boiling-resistant, highly transparent and high-barrier cyclic olefin copolymer film of the present invention comprises the following steps:

[0028] (1) Modification of binary random copolymer polypropylene and ternary random copolymer polypropylene:

[0029] Nano-silicon dioxide is added to binary random copolymer polypropylene and ternary random copolymer polypropylene respectively, and the mixture is extruded and granulated through a twin-screw water-cooling unit;

[0030] (2) After mixing the raw materials of the outer layer, the middle layer and the inner layer according to the ratio, the materials are extruded and granulated by a twin-screw water-cooling unit;

[0031] (3) After three-layer co-extrusion blow molding, a boiling-resistant, highly transparent, and high-barrier cycloolefin copolymer film is obtained.

[0032] The amount of nano-silicon dioxide added in step (1) is: 0.2-1.5 parts by mass of nano-silicon dioxide is added for every 100 parts by mass of binary random copolymer polypropylene and ternary random copolymer polypropylene.

[0033] The screw temperature of the twin-screw water-cooled unit for extrusion granulation in step (1) is 190-220° C., and the screw speed is 50 rpm.

[0034] The screw temperature of the twin-screw water-cooled unit for extrusion granulation in step (2) is 190-220° C., and the screw speed is 50 rpm.

[0035] The screw temperature of the blow molding in step (3) is 190-230°C, and the screw speed is 50 rpm.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] (1) The present invention adopts a three-layer co-extrusion method, utilizes the characteristics of the multi-layer film structure, and uses a high-performance modified COP layer as the outer layer to solve the problem of reduced transmittance caused by the high-temperature ring opening of ethylene monomer and norbornene in COC and the formation of hydroxyl groups with water molecules. After the cycloolefin copolymer film is sterilized at a high temperature of 121°C, the transmittance of the product reaches more than 92%.

[0038] (2) The present invention adds layered double hydroxide to the outer layer and the middle layer to improve the oxygen barrier property of the cycloolefin copolymer.

[0039] (3) The present invention adds nano-scale silicon dioxide to binary polypropylene and ternary polypropylene to improve the crystallinity of polypropylene, accelerate the crystallization rate, and make the crystal form finer; improve the light transmittance of the material after processing, and cooperate with layered double hydroxide to improve the barrier properties between the layers.

[0040] (4) The method of the present invention is simple and easy to implement and suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 Figure 2 is a layer structure diagram of cyclic olefin copolymer film. DETAILED DESCRIPTION

[0042] The present invention will be further described below with reference to the embodiments.

[0043] Unless otherwise specified, all raw materials used in the examples are commercially available.

[0044] COC is 8007F-600, purchased from Polyplastics Co., Ltd.

[0045] COP is ZEONEX1020R, purchased from Zeon Corporation of Japan;

[0046] Nano-silicon dioxide: size 30±5nm; Bohuasi Nano-Tech (Ningbo) Co., Ltd.;

[0047] SEBS is YH-503, purchased from Yueyang Baling Jiayun Petrochemical Co., Ltd.;

[0048] POE is Exact9182, purchased from ExxonMobil;

[0049] TPU is HF-1380A, purchased from Huafeng Group Co., Ltd.

[0050] The binary random copolymer polypropylene is SC876CF, purchased from Borealis;

[0051] The terpolymer random copolymer polypropylene is SFC-750D, purchased from Lotte Chemical in South Korea;

[0052] Magnesium aluminum layered double hydroxide was purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.

[0053] Example 1

[0054] The preparation process of the boiling-resistant, highly transparent and high-barrier cyclic olefin copolymer film comprises the following steps:

[0055] (1) Modification of binary random copolymer polypropylene and ternary random copolymer polypropylene:

[0056] 0.5 parts by weight of nano-silicon dioxide were added to 100 parts by weight of binary random copolymer polypropylene and 100 parts by weight of ternary random copolymer polypropylene, and granulated by twin-screw extrusion, wherein the temperatures of the screw zones were 190° C., 210° C., 220° C., 220° C., 220° C., and 210° C. in sequence;

[0057] (2) After the materials of each layer are mixed evenly, a twin-screw extruder is used for granulation. The temperatures of each zone of the extruder are 170°C, 180°C, 210°C, 220°C, 220°C, and 200°C. The mass proportions of the raw materials of each layer are as follows:

[0058] The inner layer is composed of 70.0 parts of COC, 20.0 parts of SEBS, and 10.0 parts of modified ternary random copolymer polypropylene;

[0059] The middle layer is composed of 64.0 parts of COC, 25.0 parts of SEBS, 10.0 parts of modified binary random copolymer polypropylene, and 1.0 parts of magnesium aluminum layered double hydroxide;

[0060] The outer layer is composed of 64.0 parts of COP, 25.0 parts of SEBS, 10.0 parts of modified binary random copolymer polypropylene, and 1.0 parts of magnesium aluminum layered double hydroxide;

[0061] (3) The outer layer material, the middle layer material and the inner layer material are blown into films by a three-layer co-extrusion extruder, with the screw temperatures being 190°C, 210°C, 220°C, 220°C, and 220°C, and the die temperature being 200°C;

[0062] The total thickness of the cycloolefin copolymer film is 180 μm, of which the inner layer accounts for 20.0% of the total thickness, the middle layer accounts for 60.0% of the total thickness, and the outer layer accounts for 20.0% of the total thickness.

[0063] Example 2

[0064] The preparation process of the boiling-resistant, highly transparent and high-barrier cyclic olefin copolymer film comprises the following steps:

[0065] (1) Modification of binary random copolymer polypropylene and ternary random copolymer polypropylene:

[0066] 0.5 parts by weight of nano-silicon dioxide were added to 100 parts by weight of binary random copolymer polypropylene and 100 parts by weight of ternary random copolymer polypropylene, and granulated by twin-screw extrusion, wherein the temperatures of the screw zones were 190° C., 210° C., 220° C., 220° C., 220° C., and 210° C. in sequence;

[0067] (2) After the materials of each layer are mixed evenly, a twin-screw extruder is used for granulation. The temperatures of each zone of the extruder are 170°C, 180°C, 210°C, 220°C, 220°C, and 200°C. The mass proportions of the raw materials of each layer are as follows:

[0068] The inner layer is composed of 70.0 parts of COC, 20.0 parts of POE, and 10.0 parts of modified ternary random copolymer polypropylene;

[0069] The middle layer is composed of 64.0 parts of COC, 25.0 parts of POE, 10.0 parts of modified binary random copolymer polypropylene, and 1.0 parts of magnesium aluminum layered double hydroxide;

[0070] The outer layer is composed of 64.0 parts of COP, 25.0 parts of POE, 10.0 parts of modified binary random copolymer polypropylene, and 1.0 parts of magnesium aluminum layered double hydroxide;

[0071] (3) The outer layer material, the middle layer material and the inner layer material are blown into films by a three-layer co-extrusion extruder, with the screw temperatures being 190°C, 210°C, 220°C, 220°C, and 220°C, and the die temperature being 200°C;

[0072] The total thickness of the cycloolefin copolymer film is 180 μm, of which the inner layer accounts for 20.0% of the total thickness, the middle layer accounts for 60.0% of the total thickness, and the outer layer accounts for 20.0% of the total thickness.

[0073] Example 3

[0074] The preparation process of the boiling-resistant, highly transparent and high-barrier cyclic olefin copolymer film comprises the following steps:

[0075] (1) Modification of binary random copolymer polypropylene and ternary random copolymer polypropylene:

[0076] 0.5 parts by weight of nano-silicon dioxide were added to 100 parts by weight of binary random copolymer polypropylene and 100 parts by weight of ternary random copolymer polypropylene, and granulated by twin-screw extrusion, wherein the temperatures of the screw zones were 190° C., 210° C., 220° C., 220° C., 220° C., and 210° C. in sequence;

[0077] (2) After the materials of each layer are mixed evenly, a twin-screw extruder is used for granulation. The temperatures of each zone of the extruder are 170°C, 180°C, 210°C, 220°C, 220°C, and 200°C. The mass proportions of the raw materials of each layer are as follows:

[0078] The inner layer is composed of 70.0 parts of COC, 20.0 parts of TPU, and 10.0 parts of modified ternary random copolymer polypropylene;

[0079] The middle layer is composed of 64.0 parts of COC, 25.0 parts of TPU, 10.0 parts of modified binary random copolymer polypropylene, and 1.0 parts of magnesium aluminum layered double hydroxide;

[0080] The outer layer is composed of 64.0 parts of COP, 25.0 parts of TPU, 10.0 parts of modified binary random copolymer polypropylene, and 1.0 parts of magnesium aluminum layered double hydroxide;

[0081] (3) The outer layer material, the middle layer material and the inner layer material are blown into films by a three-layer co-extrusion extruder with screw temperatures of 190°C, 210°C, 220°C, 220°C, and 220°C and a die temperature of 200°C.

[0082] The total thickness of the cycloolefin copolymer film is 180 μm, of which the inner layer accounts for 20.0% of the total thickness, the middle layer accounts for 60.0% of the total thickness, and the outer layer accounts for 20.0% of the total thickness.

[0083] Example 4

[0084] The preparation process of the boiling-resistant, highly transparent and high-barrier cyclic olefin copolymer film comprises the following steps:

[0085] (1) Modification of binary random copolymer polypropylene and ternary random copolymer polypropylene:

[0086] 0.5 parts by weight of nano-silicon dioxide were added to 100 parts by weight of binary random copolymer polypropylene and 100 parts by weight of ternary random copolymer polypropylene, and granulated by twin-screw extrusion, wherein the temperatures of the screw zones were 190° C., 210° C., 220° C., 220° C., 220° C., and 210° C. in sequence;

[0087] (2) After the materials of each layer are mixed evenly, a twin-screw extruder is used for granulation. The temperatures of each zone of the extruder are 170°C, 180°C, 210°C, 220°C, 220°C, and 200°C. The mass proportions of the raw materials of each layer are as follows:

[0088] The inner layer is composed of 70.0 parts of COC, 20.0 parts of SEBS, and 10.0 parts of modified ternary random copolymer polypropylene;

[0089] The middle layer is composed of 62.0 parts of COC, 25.0 parts of SEBS, 10.0 parts of modified binary random copolymer polypropylene, and 3.0 parts of magnesium aluminum layered double hydroxide;

[0090] The outer layer is composed of 62.0 parts of COP, 25.0 parts of SEBS, 10.0 parts of modified binary random copolymer polypropylene, and 3.0 parts of magnesium aluminum layered double hydroxide;

[0091] (3) The outer layer material, the middle layer material and the inner layer material are blown into films by a three-layer co-extrusion extruder, with the screw temperatures being 190°C, 210°C, 220°C, 220°C, and 220°C, and the die temperature being 200°C;

[0092] The total thickness of the cycloolefin copolymer film is 180 μm, of which the inner layer accounts for 20.0% of the total thickness, the middle layer accounts for 60.0% of the total thickness, and the outer layer accounts for 20.0% of the total thickness.

[0093] Example 5

[0094] The preparation process of the boiling-resistant, highly transparent and high-barrier cyclic olefin copolymer film comprises the following steps:

[0095] (1) Modification of binary random copolymer polypropylene and ternary random copolymer polypropylene:

[0096] 0.5 parts by weight of nano-silicon dioxide were added to 100 parts by weight of binary random copolymer polypropylene and 100 parts by weight of ternary random copolymer polypropylene, and granulated by twin-screw extrusion, wherein the temperatures of the screw zones were 190° C., 210° C., 220° C., 220° C., 220° C., and 210° C. in sequence;

[0097] (2) After the materials of each layer are mixed evenly, a twin-screw extruder is used for granulation. The temperatures of each zone of the extruder are 170°C, 180°C, 210°C, 220°C, 220°C, and 200°C. The mass proportions of the raw materials of each layer are as follows:

[0098] The inner layer is composed of 70.0 parts of COC, 20.0 parts of SEBS, and 10.0 parts of modified ternary random copolymer polypropylene;

[0099] The middle layer is composed of 63.0 parts of COC, 25.0 parts of SEBS, 10.0 parts of modified binary random copolymer polypropylene, and 2.0 parts of magnesium aluminum layered double hydroxide;

[0100] The outer layer is composed of 63.0 parts of COP, 25.0 parts of SEBS, 10.0 parts of modified binary random copolymer polypropylene, and 2.0 parts of magnesium aluminum layered double hydroxide;

[0101] (3) The outer layer material, the middle layer material and the inner layer material are blown into films by a three-layer co-extrusion extruder with screw temperatures of 190°C, 210°C, 220°C, 220°C, and 220°C and a die temperature of 200°C.

[0102] The total thickness of the cycloolefin copolymer film is 180 μm, of which the inner layer accounts for 20.0% of the total thickness, the middle layer accounts for 60.0% of the total thickness, and the outer layer accounts for 20.0% of the total thickness.

[0103] Example 6

[0104] The preparation process of the boiling-resistant, highly transparent and high-barrier cyclic olefin copolymer film comprises the following steps:

[0105] (1) Modification of binary random copolymer polypropylene and ternary random copolymer polypropylene:

[0106] 1.5 parts by weight of nano-silicon dioxide were added to 100 parts by weight of binary random copolymer polypropylene and 100 parts by weight of ternary random copolymer polypropylene, and granulated by twin-screw extrusion. The temperatures of the screw zones were 190° C., 210° C., 220° C., 220° C., 220° C., and 210° C. in sequence.

[0107] (2) After the materials of each layer are mixed evenly, a twin-screw extruder is used for granulation. The temperatures of each zone of the extruder are 170°C, 180°C, 210°C, 220°C, 220°C, and 200°C. The mass proportions of the raw materials of each layer are as follows:

[0108] The inner layer is composed of 80.0 parts of COC, 10.0 parts of SEBS, and 10.0 parts of modified ternary random copolymer polypropylene;

[0109] The middle layer is composed of 60.0 parts of COC, 29.0 parts of SEBS, 10.0 parts of modified binary random copolymer polypropylene, and 1.0 parts of magnesium aluminum layered double hydroxide;

[0110] The outer layer is composed of 60.0 parts of COP, 29.0 parts of SEBS, 10.0 parts of modified binary random copolymer polypropylene, and 1.0 parts of magnesium aluminum layered double hydroxide;

[0111] (3) The outer layer material, the middle layer material and the inner layer material are blown into films by a three-layer co-extrusion extruder, with the screw temperatures being 190°C, 210°C, 220°C, 220°C, and 220°C, and the die temperature being 200°C;

[0112] The total thickness of the cycloolefin copolymer film is 175 μm, of which the inner layer accounts for 15.0% of the total thickness, the middle layer accounts for 70.0% of the total thickness, and the outer layer accounts for 15.0% of the total thickness.

[0113] Example 7

[0114] The preparation process of the boiling-resistant, highly transparent and high-barrier cyclic olefin copolymer film comprises the following steps:

[0115] (1) Modification of binary random copolymer polypropylene and ternary random copolymer polypropylene:

[0116] 0.2 parts by weight of nano-silicon dioxide were added to 100 parts by weight of binary random copolymer polypropylene and 100 parts by weight of ternary random copolymer polypropylene, and granulated by twin-screw extrusion. The temperatures of the screw zones were 190° C., 210° C., 220° C., 220° C., 220° C., and 210° C. in sequence.

[0117] (2) After the materials of each layer are mixed evenly, a twin-screw extruder is used for granulation. The temperatures of each zone of the extruder are 170°C, 180°C, 210°C, 220°C, 220°C, and 200°C. The mass proportions of the raw materials of each layer are as follows:

[0118] The inner layer is composed of 75.0 parts of COC, 15.0 parts of SEBS, and 10.0 parts of modified ternary random copolymer polypropylene;

[0119] The middle layer is composed of 69.0 parts of COC, 20.0 parts of SEBS, 10.0 parts of modified binary random copolymer polypropylene, and 1.0 parts of magnesium aluminum layered double hydroxide;

[0120] The outer layer is composed of 69.0 parts of COP, 20.0 parts of SEBS, 10.0 parts of modified binary random copolymer polypropylene, and 1.0 parts of magnesium aluminum layered double hydroxide;

[0121] (3) The outer layer material, the middle layer material and the inner layer material are blown into films by a three-layer co-extrusion extruder, with the screw temperatures being 190°C, 210°C, 220°C, 220°C, and 220°C, and the die temperature being 200°C;

[0122] The total thickness of the cycloolefin copolymer film is 225 μm, of which the inner layer accounts for 25.0% of the total thickness, the middle layer accounts for 50.0% of the total thickness, and the outer layer accounts for 25.0% of the total thickness.

[0123] Comparative Example 1

[0124] The preparation process of the boiling-resistant, highly transparent and high-barrier cyclic olefin copolymer film comprises the following steps:

[0125] (1) Modification of binary random copolymer polypropylene and ternary random copolymer polypropylene:

[0126] 0.5 parts by weight of nano-silicon dioxide were added to 100 parts by weight of binary random copolymer polypropylene and 100 parts by weight of ternary random copolymer polypropylene, and granulated by twin-screw extrusion, wherein the temperatures of the screw zones were 190° C., 210° C., 220° C., 220° C., 220° C., and 210° C. in sequence;

[0127] (2) After the materials of each layer are mixed evenly, a twin-screw extruder is used for granulation. The temperatures of each zone of the extruder are 170°C, 180°C, 210°C, 220°C, 220°C, and 200°C. The mass proportions of the raw materials of each layer are as follows:

[0128] The inner layer is composed of 90.0 parts of COC and 10.0 parts of modified ternary random copolymer polypropylene;

[0129] The middle layer is composed of 90.0 parts of COC and 10.0 parts of modified binary random copolymer polypropylene;

[0130] The outer layer is composed of 90.0 parts of COC and 10.0 parts of modified binary random copolymer polypropylene;

[0131] (3) The outer layer material, the middle layer material and the inner layer material are blown into films by a three-layer co-extrusion extruder, with the screw temperatures being 190°C, 210°C, 220°C, 220°C, and 220°C, and the die temperature being 200°C;

[0132] The total thickness of the cycloolefin copolymer film is 180 μm, of which the inner layer accounts for 20.0% of the total thickness, the middle layer accounts for 60.0% of the total thickness, and the outer layer accounts for 20.0% of the total thickness.

[0133] Comparative Example 2

[0134] The preparation process of the boiling-resistant, highly transparent and high-barrier cyclic olefin copolymer film comprises the following steps:

[0135] (1) Modification of binary random copolymer polypropylene and ternary random copolymer polypropylene:

[0136] 0.5 parts by weight of nano-silicon dioxide were added to 100 parts by weight of binary random copolymer polypropylene and 100 parts by weight of ternary random copolymer polypropylene, and granulated by twin-screw extrusion, wherein the temperatures of the screw zones were 190° C., 210° C., 220° C., 220° C., 220° C., and 210° C. in sequence;

[0137] (2) After the materials of each layer are mixed evenly, a twin-screw extruder is used for granulation. The temperatures of each zone of the extruder are 170°C, 180°C, 210°C, 220°C, 220°C, and 200°C. The mass proportions of the raw materials of each layer are as follows:

[0138] The inner layer is composed of 90.0 parts of COC and 10.0 parts of modified ternary random copolymer polypropylene;

[0139] The middle layer is composed of 90.0 parts of COC and 10.0 parts of modified binary random copolymer polypropylene;

[0140] The outer layer is composed of 90.0 parts of COP and 10.0 parts of modified binary random copolymer polypropylene;

[0141] (3) The outer layer material, the middle layer material and the inner layer material are blown into films by a three-layer co-extrusion extruder, with the screw temperatures being 190°C, 210°C, 220°C, 220°C, and 220°C, and the die temperature being 200°C;

[0142] The total thickness of the cycloolefin copolymer film is 180 μm, of which the inner layer accounts for 20.0% of the total thickness, the middle layer accounts for 60.0% of the total thickness, and the outer layer accounts for 20.0% of the total thickness.

[0143] Comparative Example 3

[0144] The preparation process of the boiling-resistant, highly transparent and high-barrier cyclic olefin copolymer film comprises the following steps:

[0145] (1) Modification of binary random copolymer polypropylene and ternary random copolymer polypropylene:

[0146] 0.5 parts by weight of nano-silicon dioxide were added to 100 parts by weight of binary random copolymer polypropylene and 100 parts by weight of ternary random copolymer polypropylene, and granulated by twin-screw extrusion, wherein the temperatures of the screw zones were 190° C., 210° C., 220° C., 220° C., 220° C., and 210° C. in sequence;

[0147] (2) After the materials of each layer are mixed evenly, a twin-screw extruder is used for granulation. The temperatures of each zone of the extruder are 170°C, 180°C, 210°C, 220°C, 220°C, and 200°C. The mass proportions of the raw materials of each layer are as follows:

[0148] The inner layer is composed of 70.0 parts of COC, 20.0 parts of SEBS, and 10.0 parts of modified ternary random copolymer polypropylene;

[0149] The middle layer is composed of 65.0 parts of COC, 25.0 parts of SEBS, and 10.0 parts of modified binary random copolymer polypropylene;

[0150] The outer layer is composed of 65.0 parts of COP, 25.0 parts of SEBS, and 10.0 parts of modified binary random copolymer polypropylene;

[0151] (3) The outer layer material, the middle layer material and the inner layer material are blown into films by a three-layer co-extrusion extruder, with the screw temperatures being 190°C, 210°C, 220°C, 220°C, and 220°C, and the die temperature being 200°C;

[0152] The total thickness of the cycloolefin copolymer film is 180 μm, of which the inner layer accounts for 20.0% of the total thickness, the middle layer accounts for 60.0% of the total thickness, and the outer layer accounts for 20.0% of the total thickness.

[0153] Comparative Example 4

[0154] The preparation process of the boiling-resistant, highly transparent and high-barrier cyclic olefin copolymer film comprises the following steps:

[0155] After the materials of each layer are evenly mixed, a twin-screw extruder is used for granulation. The extruder temperature is 190~220℃. The mass proportion of the raw materials of each layer is as follows:

[0156] The inner layer is composed of 100.0 parts of COC;

[0157] The middle layer is composed of 100.0 parts of COC;

[0158] The outer layer is composed of 100.0 parts of COC;

[0159] The outer layer material, the middle layer material and the inner layer material were blown into films by a three-layer co-extrusion extruder. The screw temperatures were 190°C, 210°C, 220°C, 220°C, and 220°C, and the die temperature was 200°C.

[0160] The total thickness of the cycloolefin copolymer film is 180 μm, of which the inner layer accounts for 20.0% of the total thickness, the middle layer accounts for 60.0% of the total thickness, and the outer layer accounts for 20.0% of the total thickness.

[0161] Comparative Example 5

[0162] The preparation process of the boiling-resistant, highly transparent and high-barrier cyclic olefin copolymer film comprises the following steps:

[0163] After the materials of each layer are evenly mixed, a twin-screw extruder is used for granulation. The extruder temperature is 190~220℃. The mass proportions of the raw materials of each layer are as follows:

[0164] The inner layer is composed of 90.0 parts of COC and 10.0 parts of ternary random copolymer polypropylene;

[0165] The middle layer is composed of 90.0 parts of COC and 10.0 parts of binary random copolymer polypropylene;

[0166] The outer layer is composed of 90.0 parts of COC and 10.0 parts of binary random copolymer polypropylene;

[0167] The outer layer material, the middle layer material and the inner layer material were blown into films by a three-layer co-extrusion extruder. The screw temperatures were 190°C, 210°C, 220°C, 220°C, and 220°C, and the die temperature was 200°C.

[0168] The total thickness of the cycloolefin copolymer film is 180 μm, of which the inner layer accounts for 20.0% of the total thickness, the middle layer accounts for 60.0% of the total thickness, and the outer layer accounts for 20.0% of the total thickness.

[0169] The cycloolefin copolymer films prepared in the examples and comparative examples were tested, and the results are shown in Tables 1-3 below:

[0170] Table 1 Mechanical properties of cycloolefin copolymer films: tensile strength (GB / T1040.3-2006), heat sealing strength (GB / T4456-2008)

[0171]

[0172] Table 2 Barrier properties of cycloolefin copolymer films (GB / T 1038-2000)

[0173]

[0174] Table 3 Light transmittance of cycloolefin copolymer film before and after cooking (GB / T2410-2008)

[0175]

[0176] The results show that the mechanical properties and barrier properties of the film of Comparative Example 1 are improved compared with those of Comparative Example 4. In terms of mechanical properties, the transverse and longitudinal tensile strength of the film of Comparative Example 4 decreased from 55MPa and 58MPa to 44MPa and 48MPa compared with Comparative Example 1, while the tensile elongation in the transverse and longitudinal directions increased from 3.5% and 2.9% to 65% and 46%. The reason for the significant change in the flexibility of the film is mainly attributed to the introduction of modified polypropylene, which enhances the flexibility of the film through the network optimization of the COC rigid segment and the PP flexible segment, and inevitably loses part of the strength of the film.

[0177] In terms of barrier properties and light transmittance, it can be seen from Comparative Examples 5 and 1 that the introduction of modified polypropylene increases the water vapor and oxygen permeability of the film from 1.4 g·100 mm / m to 2.5 g·100 mm / m respectively. 2 24hr and 24.1cm 3 100mm / m 2 24hr bar down to 1.3g 100mm / m 2 24hr and 18.8cm 3 100mm / m 2·24hr·bar, the barrier performance of the film is improved; and the light transmittance of the film after sterilization is also increased from 84.0% to 90.4%. The above performance improvement is mainly because the addition of nano-scale silicon dioxide in binary polypropylene and ternary polypropylene improves the crystallinity of polypropylene, accelerates the crystallization rate, and makes the crystal form fine, thereby improving the light transmittance and barrier performance of the material after processing.

[0178] The transmittance of the film after sterilization was further improved in Comparative Example 2, from 84% to 92.3%. Unlike Comparative Example 1, Comparative Example 2 uses high-performance modified COP as the outer layer, which effectively blocks the permeability of water vapor during cooking and solves the problem of reduced transmittance caused by high-temperature ring opening of ethylene monomers and norbornene in COC and the formation of hydroxyl groups with water molecules. This is also confirmed by the water vapor permeability test, which is reduced to 0.8g·100mm / m 2 ·24hr, compared with COC as the outer layer, it is significantly lower. Therefore, using modified COP as the outer layer material of the film can effectively improve the light transmittance of the film after steaming. However, the poor mechanical properties of the film still limit the use of COC film. Based on this, comparative example 3 introduces an elastomer into the film to further optimize the flexibility of the film. The tensile performance test results show that the tensile elongation in the horizontal and vertical directions is increased to 578% and 522%. The introduction of the elastomer effectively optimizes the tensile elongation of the COC film.

[0179] Although the above method effectively improves the problem of decreased transmittance of COC film after cooking, it still cannot reach the scope of practical use. Therefore, layered double hydroxide is added to the outer layer and middle layer of the film in Example 1, so that the barrier performance and transmittance of the COC film are significantly improved. Specifically, the water vapor and oxygen permeability of the COC film in Example 1 is reduced to 0.5g·100mm / m 2 24hr and 3.1cm 3 100mm / m 2 ·24hr·bar, and the transmittance after cooking is increased to 93.8%. Through the barrier effect of COP, the role of layered double hydroxide is coordinated to improve the barrier properties between the layers, and significantly improve the transmittance of the film after cooking. Example 1, Example 4 and Example 5 explore the effect of different amounts of magnesium aluminum layered double hydroxide on the transmittance of COC film after cooking. And through Example 1, Example 2 and Example 3, the effects of SEBS, TPU and POE elastomers on the regulation of the mechanical properties of COC film materials were verified respectively. The results show that without affecting the transmittance of the film, the introduction of SEBS elastomer has a more effective effect on improving the mechanical properties of the COC film.

Claims

1. A boiling-resistant, highly transparent, high-barrier cyclic olefin copolymer film, characterized in that: It is a three-layer co-extruded film, consisting of an inner layer, a middle layer and an outer layer, and is made of the following raw materials in parts by weight: Inner Layer: Cyclic olefin copolymer: 70.0-80.0 parts; Toughening agent: 10.0~20.0 parts; Modified ternary random copolymer polypropylene: 10 parts; Middle layer: Cyclic olefin copolymer: 60.0-70.0 parts; Toughening agent: 20.0~30.0 parts; Modified binary random copolymer polypropylene: 10 parts; Layered double hydroxide: 1.0-3.0 parts; Outer Layer: Cycloolefin polymer: 60.0-70.0 parts; Toughening agent: 20.0~30.0 parts; Modified binary random copolymer polypropylene: 10 parts; Layered double hydroxide: 1.0-3.0 parts; The total thickness of the cycloolefin copolymer film is 175-225 μm, wherein the inner layer accounts for 15.0-25.0% of the total thickness, the middle layer accounts for 50.0-70.0% of the total thickness, and the outer layer accounts for 15.0-30.0% of the total thickness; The modified binary random copolymer polypropylene and modified ternary random copolymer polypropylene are modified by introducing nano-silicon dioxide: nano-silicon dioxide is added to the binary random copolymer polypropylene and the ternary random copolymer polypropylene respectively, and extruded into granules by a twin-screw water-cooling unit; The size of the nano silicon dioxide is 25-35nm; The layered double hydroxide is magnesium-aluminum layered double hydroxide.

2. The boiling-resistant, highly transparent, high-barrier cyclic olefin copolymer film according to claim 1, characterized in that: The toughening agent is one or more of styrene-ethylene-butylene-styrene block copolymer, thermoplastic polyurethane elastomer and polyolefin elastomer.

3. A process for preparing the boiling-resistant, highly transparent and high-barrier cyclic olefin copolymer film according to any one of claims 1 to 2, characterized in that: The following steps are involved: (1) Modification of binary random copolymer polypropylene and ternary random copolymer polypropylene: Nano-silicon dioxide is added to binary random copolymer polypropylene and ternary random copolymer polypropylene respectively, and the mixture is extruded into granules through a twin-screw water-cooling unit; (2) After mixing the raw materials of the outer layer, the middle layer and the inner layer according to the ratio, the materials are extruded and granulated by a twin-screw water-cooling unit; (3) After three-layer co-extrusion blow molding, a boiling-resistant, highly transparent, and high-barrier cycloolefin copolymer film is obtained.

4. The process for preparing the boiling-resistant, highly transparent and high-barrier cyclic olefin copolymer film according to claim 3, characterized in that: The amount of nano-silicon dioxide added in step (1) is: 0.2-1.5 parts by mass of nano-silicon dioxide is added for every 100 parts by mass of binary random copolymer polypropylene and ternary random copolymer polypropylene.

5. The process for preparing the boiling-resistant, highly transparent and high-barrier cyclic olefin copolymer film according to claim 3, characterized in that: The screw temperature of the twin-screw water-cooled unit for extrusion granulation in step (1) is 190-220°C.

6. The process for preparing the boiling-resistant, highly transparent and high-barrier cyclic olefin copolymer film according to claim 3, characterized in that: The screw temperature of the twin-screw water-cooled unit for extrusion granulation in step (2) is 190-220°C.

7. The process for preparing the boiling-resistant, highly transparent and high-barrier cyclic olefin copolymer film according to claim 3, characterized in that: The screw temperature of the blow molding in step (3) is 190-230°C.

Citation Information

Patent Citations

  • High-barrier single polymeric membrane and preparation method thereof

    CN115384149A

  • FFS (fringe field switching) heavy packaging film

    CN115534462A